2021
DOI: 10.1037/apl0000873
|View full text |Cite
|
Sign up to set email alerts
|

Words that hurt: Leaders’ anti-Asian communication and employee outcomes.

Abstract: With the outbreak of COVID-19, there have been growing reports of racial harassment targeting Asian Americans. We study one such manifestation of racial harassment that Asian employees may face in the workplace: Leaders' use of stigmatizing labels for COVID-19 such as the "Chinese Virus" and "Kung Flu." Integrating organizational justice theories with research on racial harassment in the workplace, we theorize that leaders' use of stigmatizing COVID-19 labels reduces employees' perceptions of interpersonal jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 71 publications
(115 reference statements)
0
32
0
Order By: Relevance
“…Finally, future studies should extend the racial backlash effects to other marginalized groups. For example, although Asian are stereotypically viewed as being posited in some high-status and high-wage occupations, such as health and high-tech industries (Koenig & Eagly, 2014), preliminary evidence has shown the discrimination toward Asian employees are shown in different formats (Jun & Wu, 2021). Applying the EVT, the negative stereotypes related to warmth and foreignness for Asian employees, may cause racial backlashes when they engage in relationship-focused impression management tactics.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, future studies should extend the racial backlash effects to other marginalized groups. For example, although Asian are stereotypically viewed as being posited in some high-status and high-wage occupations, such as health and high-tech industries (Koenig & Eagly, 2014), preliminary evidence has shown the discrimination toward Asian employees are shown in different formats (Jun & Wu, 2021). Applying the EVT, the negative stereotypes related to warmth and foreignness for Asian employees, may cause racial backlashes when they engage in relationship-focused impression management tactics.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, leaders' safety commitment positively moderated the relationship between employees' job reattachment and job engagement (Yuan et al, 2021). In contrast, research by Jun and Wu (2021) found that the leaders' use of stigmatizing COVID‐19 labels during the pandemic crisis, which were racist toward the Asian community, reduced work engagement (as well as increased emotional exhaustion of employees) by lowering perceptions of interpersonal justice at work. Although these effects were more pronounced for Asian employees, they were also present for non‐Asian employees indicating employees, overall, reacted negatively to the use of stigmatizing language in the context of the crisis.…”
Section: Setting the Scene: What Have We Learned About Organizational...mentioning
confidence: 92%
“…In a qualitative study of 763 academic women in science, technology, engineering, and medicine (STEM), Kossek et al (2021) uncovered how work–nonwork boundaries were disrupted during the pandemic as well as the different strategies that women engaged in to adapt. Using a two-study design, Jun and Wu (2021) examined leaders’ use of stigmatizing labels for the pandemic, uncovering how anti-Asian communication affects employee justice perceptions, burnout, and work engagement. Also using a multistudy design, Taylor et al (2021) focused on how employees who display physical signs of sickness at work are subject to interpersonal mistreatment (avoidance and incivility) by coworkers.…”
Section: Covid-19 Call For Papers With Rapid Reviewmentioning
confidence: 99%
“…4Eight articles (Jun & Wu, 2021; Kim et al, 2021; Liu et al, 2021; Sergent & Stajkovic, 2020; Shao, Fang, et al, 2021; Taylor et al, 2021; Vaziri et al, 2020; Zhong et al, 2021) included two studies and two articles (Hu et al, 2020; Yuan, Cockburn, et al, 2021) included three studies (total k = 62).…”
mentioning
confidence: 99%